DEVELOPMENT OF INTEGRATIVE CHARACTERISTICS TEACHER IN THE CONDITIONS OF PROFILE TRAINING FOREIGN LANGUAGE FOR FUTURE ENGINEERS (Pedagogy of Higher and Secondary Education, 2022)
The teacher integrative characteristics as the English Language education process managers are thought to be the wholeunity of their professional activity psychological, pedagogical and subject components, necessary for the integration processimplementation on the level of English Language various subject links.